Effect of hexane extract of spinach in the removal of arsenic from rat - Badar Uddin Umar (Bangladesh Pharmacological Society, 2007)
Extensive search is going on for a cheap, easily available and effective remedy of chronic arsenic poisoning. The present study was designed to find the effects of hexane extract of spinach in the removal of arsenic from arsenic treated rat. Rats were fed arsenic trioxide through Ryles tube for one month then they were fed on hexane extract (1-4%) of spinach for another one month. Hexane extract of spinach decreased accumulated arsenic from rat liver, spleen, kidney, intestine, lungs and skin significantly. Besides, it reduced the oxidative stress caused by arsenic which was evident by decreased levels of malondialdehye (MDA) in the above tissues. Hexane extract decreases both arsenic level and MDA level in rat tissues in dose dependent manner, which is more effective at lower doses.